ZAKAT AND ISLAMIC MICROFINANCE INTEGRATION FOR RURAL POVERTY ALLEVIATION IN NORTHERN NIGERIA - Ifeoma Okechukwu; Uchechi Akinyi; Samuel Ayodele; Chinonso Onyema (Yayasan Adra Karima Hubbi, 2025)
Poverty remains a persistent challenge in Northern Nigeria, where rural communities face limited access to formal financial services, weak economic infrastructure, and high unemployment rates. Zakat, as a pillar of Islamic social finance, has historically served as a mechanism for wealth redistribution, while Islamic microfinance offers interest-free financial inclusion tools for underserved populations. Despite their individual strengths, these instruments are often implemented in isolation, limiting their long-term impact on poverty alleviation. This study aims to investigate the integration of zakat and Islamic microfinance as a comprehensive and sustainable model for rural poverty reduction in Northern Nigeria. A mixed-methods approach was adopted, combining qualitative interviews with zakat administrators, microfinance practitioners, and rural beneficiaries, alongside a survey of 250 households across three rural districts. Results indicate that the combined model enhances both short-term welfare and long-term financial independence by linking zakat-based capital injection with microfinance schemes focused on capacity building, entrepreneurship, and risk-sharing. The study concludes that zakat-microfinance integration is not only feasible but essential for achieving inclusive economic development in Islamic contexts. Policy recommendations emphasize institutional coordination, regulatory support, and community engagement to scale the model.